A Happy Marriage: The Union of Online Instruction and Community-Based Learning. (2nd September 2016) - Lee, Jason W.; Kane, Jennifer J.; Gregg, Elizabeth A.
Abstract : This article explores the opportunities and challenges that university instructors and students have when completing course assignments that merge community-based learning (CBL) and online learning (OL) in sport management and athletic administration pedagogy. As online instruction continues to increase, instructors and students need to be equipped to handle its challenges while at the same time seeking to maximize the opportunities that result from the flexibility and versatility of online instructional methods. While both OL and CBL are popular pedagogical activities, strategic efforts need to be utilized to make these methods can compatible. This article identifies two sample projects that show how online instruction and community-based learning can be "married" in a joint union that will be beneficial for all involved.